2013
DOI: 10.1007/s13594-013-0140-7
|View full text |Cite
|
Sign up to set email alerts
|

Contamination of raw milk with Bacillus cereus from farm to retail in Abidjan, Côte d’Ivoire and possible health implications

Abstract: In Africa, milk and dairy products play an important role in human nutrition but could represent a risk to human health, due to poor hygiene throughout the production chain. This study aimed firstly to assess the contamination of raw milk produced in traditional dairy farms in Abidjan with Bacillus cereus from farm to retail and secondly to assess the associated health risk for consumers in informal markets using a participatory approach. In total, 320 samples including 150 milk samples were collected in 15 pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 4 publications
1
17
0
Order By: Relevance
“…The contamination of milk and other dairy products with B. cereus is a common problem due to its effect on the quality of the products and the potential health hazards of the presence of toxigenic strains [21]. In the current study, two out of seven raw milk samples were found to be contaminated with toxigenic B. cereus.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…The contamination of milk and other dairy products with B. cereus is a common problem due to its effect on the quality of the products and the potential health hazards of the presence of toxigenic strains [21]. In the current study, two out of seven raw milk samples were found to be contaminated with toxigenic B. cereus.…”
Section: Discussionmentioning
confidence: 68%
“…In the current study, two out of seven raw milk samples were found to be contaminated with toxigenic B. cereus. Other studies reported relatively high percentage of B. cereus contamination of raw milk [15,21,22]. The source of contamination of raw milk samples is probably the soil in the milking area, feed and bedding material could be as well potential sources of contamination [21,22] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pathogenic are responsible the damage on health of consumers and comes mainly from human, animals and environment (Edalati et al, 2019). Thus, Bacillus cereus, Campylobacter, Clostridium, Escherichia coli, Listeria monocytogenes, Salmonella and Staphylococcus are the pathogens frequently found in milk (Yobouet et al, 2014;Amenu et al, 2019). These microorganisms are the origin of food poisoning and digestive disorders.…”
Section: Discussionmentioning
confidence: 99%
“…It must be noted that the risk of food poisoning from street food remains a threat in many parts of the world, especially microbiological contamination. Bacillus cereus contamination of raw milk produced on traditional dairy farms in Abidjan (Ivory Coast) from farm to retail was estimated at 27% and 41% respectively, for the udder milk samples and from seller's pooled milk (Yobouet et al, 2013). Given the high degree of milk consumption, there is a risk of exposure to B. cereus and therefore the probability of food poisoning caused by this bacterium is high.…”
Section: Bacillus Cereus In Africa's Street Foodsmentioning
confidence: 99%